Technology of compression on the base of method of code of binary sequences due to the amount of bit transitions - Гумен, Микола Борисович; Юдін, Олександр Костянтинович; Курінь, Ксенія Олександрівна (Ukrainian Information Security Research Journal, 2012)
The method of compression of images on the base of coding of binary sequences due the amount of bit changes is offered.The prototype of structure of coder is formed. The choice of method of transformation of component of image and is proved. The choice of method of coding of transforms is proved. The structural model of procedure of compression of images taking into account the method of coding on the base of the amount of bit transitions is developed.